Thermophysical properties and applications of nano-enhanced PCMs: An update review. (15th June 2020) - Yang, Liu; Huang, Jia-nan; Zhou, Fengjiao
Highlights: PCM is a solution to reduce energy consumption and greenhouse gas emissions. Evaluating the techniques used for the addition of nanoparticles to PCMs. Discussing on effects of nanoparticles on the thermophysical properties of PCMs. Examining the applications of nano-PCMs. Phase change rate increases with the addition of nanoparticles. Abstract: Energy conservation management using latent heat storage (LHS) technique is nowadays employed as a solution to reduce energy consumption and greenhouse gas emissions. Phase change materials (PCMs) are the main candidate for LHS method. The main focus of this study is to evaluate the techniques used for the addition of nanoparticles to PCMs. The present paper is divided into three parts. The first part summarizes PCMs and nanoparticles. In the second part, the effects of nanoparticles on the most important thermophysical properties of PCMs are discussed. In the third part, the applications of nano-PCMs (NPCMs) in the fields such as thermal energy storage (TES), thermal control unit (TCU), photovoltaic thermal (PVT), solar still (SS) and building are examined. In general, all studies show that the phase change rate increases with the addition of nanoparticles. This means that the amount of energy stored/released during the phase change process is improved.